Remifentanil Anesthesia on the Expression of Apoptosis-Related Proteins Bcl-2 and Bax in Rat Myocardial Cells with Ischemia-Reperfusion Injury - Li, Jie; Wang, Shuguang; Huang, Shaoyan; Shao, Wei; Zhang, Jianzhong (Cellular and Molecular Biology, 2022)
Ischemia-reperfusion damage to the myocardium is inevitable. This study mainly explored the effect of remifentanil anesthesia on the expression of apoptosis-related proteins Bcl-2 and Bax in rat myocardial ischemia-reperfusion injury. Select 48 mice (n=6). First, prepare solutions of different concentrations of remifentanil. A model of ischemia-reperfusion cardiomyocytes was established, and 6 slices of tissue were taken from each specimen, and the positive cells were observed with an optical microscope and magnified 100 times. Bcl-2 and Bax were positive in the cytoplasm and yellowish-brown particles in the inner membrane. According to the distribution of positive cells, randomly select 3 clear fields of view from each part, count the number of positive cells in each field, and then take the average of the proportion of positive cells to get Bcl-2 or Bax protein-positive Index (PEI). Comparison of mRNA levels in each group: Compared with the R3 group, the ratio of the M, R1, and R2 groups increased, and the mRNA expression level of the M group increased almost 3 times, P<0.05. The results of the study show that remifentanil reduces the mortality of myocardial cells by regulating the appearance of Bcl-2 and Bax proteins, and has a certain protective effect on the rat heart during myocardial ischemia and reperfusion. There is no statistically significant difference in the protective effect of remifentanil on myocardial ischemia-reperfusion.